Evaluasi Kualitas Minyak Hasil Penggorengan pada Bahan Pangan - Arsyad, Muh (JASATHP: Jurnal Sains dan Teknologi Hasil Pertanian, 2023)
Quality standards for cooking oil are important to determine the quality of the oil. There are several factors that determine quality standards, namely water and impurity content in oil, free fatty acid content, color and peroxide value. The aim of this research is to determine the effect of fried food ingredients on the quality of frying oil and the panelists' acceptance of the organoleptic test of frying oil. This research consisted of 3 treatments and 3 repetitions, where the first treatment was M1 with oil from frying fish, M2 with oil from frying bananas, and M3 oil from frying tofu. The oil quality parameters observed were free fatty acids, peroxide value, water content and organoleptics which included color, aroma and viscosity of the frying oil. This study used a completely randomized design (CRD). The research results showed that the use of different food ingredients had a significant effect on the free fatty acid content, peroxide value and water content of the frying oil. For the organoleptic test, it was found that the treatment preferred by the panelists was the M2 treatment using oil from frying bananas and the one least liked by the panelists was the M1 treatment using oil from frying fish.